A GUIDELINE PROPOSAL FOR DETERMINING DESIGN CRITERIA OF NEW BUILDING DESIGNS IN HISTORICAL CITIES: ICOMOS AND UNESCO - TOPRAK, Gizem Kuçak (SSD Journal, 2020)
The design features of the new buildings to be designed in historical cities are discussed in detail nowadays, and various rules are tried to be determined. It is tried to answer questions such as whether the new building should be designed in an old city, it should resemble the old one, how much should it be similar, should it reflect the characteristics of the age. The main reason for the controversy of the issue is the concern about the damage of historical cities concerning protecting historical cities. Especially with the concept of tangible cultural heritage and the development of the idea that this heritage is a common heritage of all cultures, it has become a matter of making joint decisions together regarding new structures to be designed in historical cities. Especially with the development of the idea that imitation of historical buildings is perceived as a disrespect to history, it has become essential to determine the limits of designing the new building with modern features without harming the historical environment. This study aims to determine these limits and to create a guideline for the determined limits and for various detailed arrangements.